1989
DOI: 10.1139/y89-219
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of a combination of clonidine and propranolol in conscious cirrhotic rats

Abstract: The hemodynamic effects of the combination of clonidine and propranolol were studied in conscious rats with portal hypertension owing to secondary biliary cirrhosis. Pressure and blood flow measurements (radioactive microsphere method) were performed in three groups of eight rats before and after drug administration. The combined effects of clonidine (2 micrograms/100 g body wt., i.v.) and propranolol (0.2 mg/min for 10 min) were compared with those observed after administration of either clonidine alone or pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 1 publication
2
7
0
Order By: Relevance
“…We found a decrease in renal blood flow in the propranolol‐treated animals. Although this is in accordance with previous reports, 20 its significance is unknown.…”
Section: Discussionsupporting
confidence: 93%
“…We found a decrease in renal blood flow in the propranolol‐treated animals. Although this is in accordance with previous reports, 20 its significance is unknown.…”
Section: Discussionsupporting
confidence: 93%
“…Several clinical and animal studies have shown that combination of vasocontrictors and vasodilators does indeed offer additional haemodynamic benefits in reversing portal hypertension or averting side-effects. Combination regimens such as vasopressin plus nitroglycerin [26][27][28], terlipressin plus propranolol [29], vasopressin plus ketanserin [30], octreotide plus nitrates [31], propranolol plus nitroglycerin [32], spironolactone plus nitrates [33], propranolol plus clonidine [34] and propranolol plus ketanserin [35] have been observed to be of benefit. On the other hand, combination regimens such as vasopressin plus clonidine [36], propranolol plus furosemide [37], propranolol plus spironolactone [38], octreotide plus propranolol [20] or octreotide plus prazosin (the present study) did not suggest any benefit.…”
Section: Discussionmentioning
confidence: 99%
“…and vasodilators does indeed offer additional hemodynamic benefits in reversing portal hypertension or averting side effects. Combination regimens such as vasopressin plus nitroglycerin (Groszmann et al 1982;Tsai et al 1986;Gimson et al 1986), terlipressin plus propranolol (Vachiery et al 1996), vasopressin plus ketanserin (Lee et al 1992), octreotide plus nitrates (Hori et al 1994), propranolol plus nitroglycerin (Kroeger and Groszmann 1985), spironolactone plus nitrates (van de Casteele et al 1996), propranolol plus clonidine (Roulot et al 1989), and propranolol plus ketanserin (Hadengue et al 1989), have been observed to be of benefit. On the other hand, combination regimens such as vasopressin plus clonidine , propranolol plus furosemide (Sogni et al 1994), or propranolol plus spironolactone (Oberti et al 1997) did not suggest benefit.…”
Section: Discussionmentioning
confidence: 99%